Dispositivo transdérmico para o tratamento complementar do bruxismo: avaliação da qualidade de vida - Martins, Ana Luiza Hehnes Silbiger (2024)
Introduction: sleep bruxism is a movement disorder related to masseter muscle rhythmic contraction that leads to grinding and/or clenching teeth. Mechanical contractions intensify teeth compression during sleep when in comparison to vigil and may inflict chronic orofacial pain, chips, joints and dental damage. Purpose: to evaluate lidocaine plaster transposition effects in management of orofacial pain and quality of sleep in patients with sleep bruxism. Methods: a ambulatorial treatment pilot study, open-labeled, self-controlled, quantitative and qualitative. It was executed with ten volunteers diagnosed with bruxism for more than five years. The volunteers self applied the 5% lidocaine plaster nightly, in the daily dose of 350mg, for a period of 8 hours, during 30 days, Quality of sleep and pain measurement were evaluated through a self-reported questionnaire. Results: the protocol was satisfactorily adopted by nine patients. It was evidenced improvements in orofacial pain caused by sleep bruxism at 10, 20 and 30 days of treatment (p<0,001), sleep quality at the end of the intervention (p<0,005) and, as expected, jaw clenching behavior did not change (p<0,05). Conclusion: 5% lidocaine plaster transposition as a coadjutant treatment for sleep bruxism, moderate or severe, provided muscle relaxation, minimized orofacial pain, had a good acceptance and improved sleep quality, with no adverse reaction